Avoiding school suspension: Assessment of a trauma-informed intervention with court-involved, female students. Issue 3 (3rd July 2018) - Crosby, Shantel D.; Day, Angelique G.; Somers, Cheryl L.; Baroni, Beverly A.
ABSTRACT: Court-involved, female students often experience trauma and disproportionate school discipline, complicating their academic success. This mixed-method study examines students' use of and experiences with the Monarch Room (MR), a trauma-informed disciplinary alternative. The study examines service utilization, using a repeated measures analysis of variance to explore whether students ( N = 71) demonstrated statistically significant changes in time spent in the MR during the year. The study also qualitatively explores the lived experiences of students ( N = 23) and perceived impact of the MR. There was a statistically significant increase in student MR use over the observation period (alpha = 0.05, F (2, 140) = 11.44, p < 0.01, eta-squared = 0.035). Students also report positive perceptions of the MR intervention. Implications for school practice are addressed.